Hubungan Tingkat ESI (Emergency Severity Index) dengan Kepuasan Pasien di Instalasi Gawat Darurat Rumah Sakit Pertamedika Ummi Rosnati - Urip Pratama; Zarra Zattira; Ellyza Fazlylawati (Lembaga Pengembangan Kinerja Dosen, 2025)
The Emergency Severity Index (ESI) is a triage method that determines the escalation of treatment for patients based on the severity of their emergency condition. In order to improve the level of satisfaction of individuals receiving health services, it is necessary to provide quality services that are responsive to the expectations and needs of patients. This study aims to explore the relationship between the ESI (Emergency Severity Index) level and patient satisfaction in the Emergency Room of Pertamedika Ummi Rosnati Hospital. The research design applied is analytical with a cross-sectional method. From a total population of 500 patients in December, 51 respondents were selected using purposive sampling. The instruments used included the ESI (Emergency Severity Index) Questionnaire and CSQ-8 (Client Satisfaction Questionnaire), with univariate and bivariate data analysis using the Chi-Square test. The results showed that in the high ESI index category, most participants (37 people or 92.5%) expressed satisfaction with the services received, while 3 people (7.5%) were dissatisfied. In the moderate ESI group, 9 respondents (90.0%) reported satisfaction, while only 1 respondent (10.0%) reported dissatisfaction. Conversely, in the mild ESI level, there were no patients who were satisfied (0%), and one patient (20.0%) was dissatisfied. Through analysis using the Chi-Square statistical test, a ρ value of 0.009 (≤ 0.05) was obtained, indicating a significant relationship between ESI levels and patient satisfaction. Based on these findings, it can be concluded that there is a correlation between ESI classification and the level of satisfaction of service users in the Emergency Department. The researchers recommend that patients gain a better understanding of the ESI stages, and the Emergency Department is expected to provide education, such as putting up informative banners related to ESI (Emergency Severity Index) to increase patient understanding of the triage process in the Emergency Department.